2016
DOI: 10.1186/s12879-016-1979-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of treatment of carbapenem-resistant Enterobacteriaceae infections and risk factors associated with outcome

Abstract: BackgroundTo describe the clinical and microbiological data of carbapenem-resistant Enterobacteriaceae (CRE) infections, the treatment used, hospital- and infection-related mortality, and risk factors for death.MethodsA prospective cohort conducted from March 2011 to December 2012. Clinical, demographic, and microbiological data such as in vitro sensitivity, clonality, carbapenemase gene mortality related to infection, and overall mortality were evaluated. Data were analyzed using Epi Info version 7.0 (CDC, At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
2
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 28 publications
7
38
2
7
Order By: Relevance
“…In this cohort, pneumonia was the most common site of infection (52 cases, 42%) and was associated with a significantly higher infection-related mortality compared with other site CRE infections (61 vs. 34.6%). 21 The same results have been confirmed by other studies reporting high mortality rates in CRE respiratory tract infections. Wang et al collected 94 cases of CRE infections from October 2010 to November 2014 in two large teaching hospitals in China.…”
Section: The Role Of Kpc In Hap and Vap And Mortalitysupporting
confidence: 78%
See 1 more Smart Citation
“…In this cohort, pneumonia was the most common site of infection (52 cases, 42%) and was associated with a significantly higher infection-related mortality compared with other site CRE infections (61 vs. 34.6%). 21 The same results have been confirmed by other studies reporting high mortality rates in CRE respiratory tract infections. Wang et al collected 94 cases of CRE infections from October 2010 to November 2014 in two large teaching hospitals in China.…”
Section: The Role Of Kpc In Hap and Vap And Mortalitysupporting
confidence: 78%
“…19,20 Giacobbe et al in a multicenter, retrospective study including 729 cases of bloodstream infections (BSIs) due to KPC-producing K. pneumoniae (KPC-Kp), found that colistin-resistant KPC-Kp were more often associated with lower respiratory tract infections and inadequate empirical antibiotic treatment than colistin-susceptible strains, leading to a higher percentage of initial treatment failure and 30-day crude mortality (51 vs. 39.4%). 21 The global epidemiology of CRE and colistin-resistant K. pneumoniae is described in ►Table 2.…”
Section: Epidemiology Of Carbapenemase-producing Enterobacteriaceaementioning
confidence: 99%
“…Furthermore, using the 2 mg/L breakpoint, no difference was found in mortality between carbapenem-resistant Enterobacteriaceae infections by colistinsusceptible and colistin-resistant isolates. 32 More important is the finding that the clinical outcomes of colistin therapy in patients infected with susceptible (MIC 2 mg/L) A. baumannii isolates but high colistin MICs (1-2 mg/L) were poorer than in patients infected with isolates with lower (,1 mg/L) MICs (7 day outcome 38% versus 20.2%, P " 0.025). 33 Finally, it was suggested that current maintenance doses may not be effective against isolates with an MIC .0.5 mg/l.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies comparing the outcomes for patients treated with monotherapy or combination therapy were reviewed, and control for confounders was taken into account. Most studies focused on or supplied data for BSI (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228)(229) (Table 4), while others included other types of infection (213,215,227,(230)(231)(232)(233)(234)(235)(236) (Table 5). Systematic reviews published in 2014 found major limitations in the studies analyzed and therefore could not draw strong conclusions (47,237).…”
Section: Monotherapy Versus Combination Therapymentioning
confidence: 99%